Model Penguatan Kepatuhan Syariah Pada Bisnis Retail Syariah Berbasis Karakter Kenabian: Integrasi Shiddiq, Amanah, Tabligh, dan Fathanah - Abu Riza Zulkarnaen; A. Rasikhu Z. Haramain (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Sharia retail business should not be reduced to the sale of halal products. It must be developed as a business ecosystem that integrates halal assurance, valid contracts, truthful information, fair pricing, consumer protection, trustworthy governance, and innovation aligned with the objectives of Islamic law. This article aims to formulate a prophetic character-based model for strengthening sharia compliance in sharia retail business by integrating shiddiq, amanah, tabligh, and fathanah. This study employs qualitative library research using a normative-conceptual approach. Primary data are derived from the Qur’an, hadith, Islamic commercial jurisprudence, Islamic business ethics literature, DSN-MUI fatwas, and halal product assurance regulations. Secondary data are obtained from books, scholarly journals, global Islamic economy reports, and contemporary studies on halal value chain, digital retail, and consumer protection. The findings show that shiddiq functions as the foundation of truthful product information, pricing, promotion, and halal claims; amanah serves as the basis of trust governance, consumer protection, data management, and business responsibility; tabligh functions as a principle of transparent, educational, and non-manipulative communication; while fathanah serves as strategic intelligence in innovation, risk management, sharia audit, and retail digitalization. This article proposes a “Prophetic Sharia Retail Model” consisting of four character pillars, eight compliance areas, twelve operational indicators, and practical SOP recommendations. The model is expected to assist Muslim retailers in building businesses that are not only halal by label, but also valid in contract, fair in transaction, trustworthy in service, and beneficial in social impact.